The influence of service procedures, transparency and security on the quality of pt umroh travel services. Fti branch muara enim - Darmin Darmin; Yelli Khairani; Yusnawati Yusnawati (Journal of Indonesian Management, 2023)
This research aims to determine the influence of service procedures, transparency and security individually on the quality of PT.FTI Muara Enim Branch Umrah travel services. The research method used in this research is a quantitative method using a questionnaire distributed to 79 respondents who were determined using random techniques. Test the instrument using validity tests, reliability tests. The results of the validity test show that the three independent variables and one dependent variable are declared valid. Meanwhile, the reliability test shows that Cronbach alpha for the four variables is declared reliable. The results of descriptive statistical analysis of the four variables show very high results. The highest variable is the service quality variable (Y). Inferential statistical analysis was carried out using classical assumption tests (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression test and T test (partial). The results of the normality test showed that all data were normally distributed. The results of the multicollinearity test did not occur and the heteroscedasticity test showed that there was no heteroscedasticity. The results of the multiple linear regression test showed that service procedures (X1) influence service quality, transparency (X2) influences service quality, security (X3) influences service quality. The results of the T test (partial) show that the service procedure (X1) H0 is rejected and H1 is accepted. Transparency variable (X2), H0 is rejected and H1 is accepted. Security variable (X3), H0 is rejected and H1 is accepted. Thus, it shows that there is a significant influence of service procedures (X1), transparency (X2) and security (X3) on the quality of PT.FTI Muara Enim Branch's Umrah travel services (Y).